Calibration of bias and scatter involved in cluster mass measurements using optical weak gravitational lensing. Issue 4 (7th September 2021) - Grandis, Sebastian; Bocquet, Sebastian; Mohr, Joseph J; Klein, Matthias; Dolag, Klaus
ABSTRACT: Cosmological inference from cluster number counts is systematically limited by the accuracy of the mass calibration, i.e. the empirical determination of the mapping between cluster selection observables and halo mass. In this work we demonstrate a method to quantitatively determine the bias and uncertainties in weak-lensing (WL) mass calibration. To this end, we extract a library of projected matter density profiles from hydrodynamical simulations. Accounting for shear bias and noise, photometric redshift uncertainties, mis-centreing, cluster member contamination, cluster morphological diversity, and line-of-sight projections, we produce a library of shear profiles. Fitting a one-parameter model to these profiles, we extract the so-called WL mass M WL . Relating the WL mass to the halo mass from gravity-only simulations with the same initial conditions as the hydrodynamical simulations allows us to estimate the impact of hydrodynamical effects on cluster number counts experiments. Creating new shear libraries for ∼1000 different realizations of the systematics provides a distribution of the parameters of the WL to halo mass relation, reflecting their systematic uncertainty. This result can be used as a prior for cosmological inference. We also discuss the impact of the inner fitting radius on the accuracy, and determine the outer fitting radius necessary to exclude the signal from neighbouring structures. Our method is currently being applied to different Stage III lensing surveys, and can easily be extended to Stage IV lensing surveys.